RETURN ON EQUITY HAS AN EFFECT ON DEBT TO EQUITY RATIO AND WORKING CAPITAL TURNOVER OF PROPERTY AND REAL ESTATE SUB-SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE (IDX) PERIOD 2018-2022 - Yono Maulana Maulana; Maya Sari; Mega Yusdian Puteri (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This study aims to determine "The Effect of Debt to Equity Ratio and Working Capital Turnover on Return On Equity in Property and Real Estate Sub-Sector Companies Listed on the Indonesian Stock Exchange (IDX) for the 2018-2022 Period". The method used in this research is a quantitative method. The population in this study is the Property and Real Estate Sub Sector. Sampling technique with purposive sampling technique. The samples in this study were 14 companies within 5 years so that 70 observational data were obtained. The data analysis technique used is multiple linear regression analysis using SPSS 25 software. The results of this study indicate that there is a significant influence between the Debt to Equity Ratio variable on Return On Equity and the Working Capital Turnover variable which has no significant effect on Return On Equity. Simultaneously the Debt to Equity Ratio and Working Capital Turnover affect Return On Equity. Keywords: Debt to Equity Ratio, Working Capital Turnover, Return On Equity